ETHNOBOTANICAL STUDY IDENTIFICATION OF PLANT TYPES THAT CAN BE USED IN ECOPRINT PRODUCTION - Nurul Fajriana; Ulia Hanum; Nurhidayatun Rahma (BIOTIK: Jurnal Ilmiah Biologi Teknologi dan Kependidikan, 2024)
ABSTRACT Used of synthetic dye in the textile industry produced liquid waste if it is not recycle with properly, it can cause pollution and contamination of water both on the surface and every drop used by humans, disrupting ecosystems and even killing life in aquatic ecosystems. Therefore, an alternative to synthetic dye is neededby using plants as natural dye. Leaves can be used for their color content, leaf bones and leaf surfaces can be used as textile motif called ecoprint. This research purposing to find out the types of plants that can be used as materials for making ecoprint as a substitute for synthetic dye and also to find out the parts of plants that can be used as materialfor making ecoprint. The research method used is descriptive qualitative from literature study and literature references regarding data and information related to research. The results showed there are 30 types of plants that can be used in ecoprint. Thishabitus plants is herbaceous, vines, shrubs, shrubs and trees. From herbaceous habitus found 5 species of plants, 3 species of vine habitus, 7 species of bush habitus, 10 species of shrub habitus and 5 species of tree habitus. The parts of plants that can be used in making ecoprints are the leaves, flowers, stems and roots. The results showed there were 30 species of plants from 21 families that could be used in making ecoprint. The parts of plant can be used in making ecoprintare parts, leaves, flowers, stems and roots, but not all parts of every type of plant can be used in the process of making ecoprint. Keywords: Ethnobotanical Studies, Ecoprint, Synthetic Dyes, Natural Dyes, HabitusREFERENCE[1] Lubis, E. F. M. D., Ghea, A., Viola, D. E, dan Soraya,  G. D. 2022. Pemanfaatan Daun dan Bunga Tanaman Buah sebagai Pewarna Motif Alami pada Media Jilbab dengan Teknik Ecoprint. Jurnal  Senashtek, hal:819-823.[2]Juniar, , S., T. dan Sulandjari S. 2018. Perbedaan Hasil Rok Pias EcoprintDaun Jati (Tectona grandis) Menggunakan Jenis dan Massa Mordan Tawas dan Cuka. Jurnal Tata Busana, 7. [3] Martani, E., Margino S. dan Nurnawati E. 2011. Isolasi Dan Karakterisasi Jamur Pendegradasi Zat Pewarna Tekstil (Isolation and Characterization of Dye-degrading Fungi). Jurnal Manusia dan Lingkungan, 18, 127-136. [4] Subagyo, P., K. & Seolistyowati. 2021. Pengaruh Zat Pewarna Sintetis terhadap Pewarnaan Kain Batik. Jurnal FOLIO. Vol. 2., No., 2. [5]Komarawidjaja, W. 2016. Sebaran Limbah Cair Industri Tekstil dan Dampaknya pada Beberapa Desa Kecamatan Rancaekek Kabupaten Bandung. Jurnal Teknologi Lingkungan. Vol. 17. No. 2., hal: 118-125. [6] Enrico. 2019. Dampak Limbah Cair Industri Tekstil Terhadap Lingkungan dan Aplikasi Tehnik Eco Printing sebagai Usaha Mengurangi Limbah. Jurnal MODA. Vol.1., No. 1. [7] Masyitoh F. dan Ernawati E. 2019. Pengaruh Mordan Tawas dan Cuka Terhadap Hasil Pewarnaan Ecoprint Bahan Katun Menggunakan Daun Jati (Tectona grandis). Gorga Jurnal Seni Rupa, 8, 387-391. [8] Saraswati, R., M. H. Dewi, S., Ratri, C. R., Fajar, D. P. 2019. Pemanfaatan Daun untuk Ecoprint dalam Menunjang Pariwisata. Depok: Departemen Geografi FMIPA UI. [9] Wirawan, B., M. Alvin. 2019. Teknik Pewarnaan Alam Ecoprint Daun Ubi dengan Penggunaan Fiksator Kapur, Tawas dan Tunjung. Jurnal Litbang Kota Pekalongan: Vol. 17:1-5. [10] Simanungkalit, Y., S. 2020. Teknik Ecoprint dengan Memanfaatkan Limbah Mawar (Rosa Sp.) pada Kain Katun. Skripsi. Semarang: UNNES. [11] Sugiyono, 2013. Metode Penelitian Pendidikan Pendekatan Kuantitatif, Kualitatif; Research & Development. Bandung: Alfabeta. [12]  Baharuddin A., Aisyah A., Saokani J. dan Risnah I. A. 2015. Karakterisasi Zat Warna Daun Jati (Tectona Grandis) Fraksi Metanol: N-Heksana sebagaiPhotosensitizer pada Dye Sensitized Solar Cell. Chimica et Natura Acta, 3. [13] Kembaren R., Putriliniar S., Maulana N., Yulianto K., Ikono r., Rochman N. T.dan Mardliyati, E. 2014. Ekstraksi dan Karakterisasi Serbuk Nano Pigmen dari Daun Tanaman Jati (Tectona grandis linn. F). Jurnal Kimia dan Kemasan, 36.[14] Sulistiawati E. dan Swastika P. 2017. Ekstraksi Zat Warna Alami dari Daun JatiMuda (Tectona grandis) dan Kayu Secang (Caesalpinia sappan) dengan Metode Ultrasound Assisted Extraction untuk Aplikasi Produk Tekstil. Skrispsi. Surabaya:InstitutTeknologi Sepuluh Nopember. [15] Koswara S. 2009. Pewarna Alami Produksi dan Penggunaannya. Ebook Pangan. [16] Haffida A. A. N. dan Rahardhian F. D. 2017. Ekstraksi Zat Tanin Dari Bahan Alami Dengan Metode Steam Extraction.Skrispsi. Surabaya:Institut Teknologi Sepuluh Nopember.